An Overview on Hitopadesa Vaidyaka - Ujitha Kuttan K; Braivin Camly R (International Journal of Ayurveda and Pharma Research, 2021)
Ayurveda, the science of life is dated back to thousands of years. In ancient times the knowledge of this system were passed orally from teachers to students. In course of time scholars began to record their knowledge in the form of treatises like Charaka Samhita, Susruta Samhita etc. Later many Acharyas composed their own treatises on the basis of knowledge they acquired as well as their own observations and experiences. Madhava Nidana, Sarangadhara Samhita, Bhavaprakasa, Kasyapa Samhita etc. are such contributions by various scholars. The ancient knowledge is updating by new physicians through the observations they made in relation with changes in Kala (time), Desa (place), availability of medicines, newly emerging diseases etc. So it is necessary to explore such treasures of knowledge.Hitopadesa vaidyaka is a work on Ayurveda which gives emphasis on the diagnosis of disease as well as treatment through simple medicinal formulations. The book starts with Ashtasthana pareeksha where Nadi pareeksha is given utmost importance and provides description of Jvara etc. diseases with brief description on Lakshana (clinical features) and detailed description on Chikitsa (treatment). The author has given priority to simple formulations using easily available Oushadhas (medicines) the effect of which are established by the author himself through his clinical experience. Some diseases mentioned in ancient treatises are not found in this text whereas some new diseases are included. As the book found worth study, this paper aims at an overview on the treatise Hitopadesa Vaidyaka.